TANTANGAN DOSEN PTKI DI ERA INDUSTRI 4.0 - Kasinyo Harto (Jurnal Tatsqif, 2018)
The current study intends to clarify the challenges of lecturers in the 4th industrial era, especially those from Islamic Higher education. This study asserts that lecturers in the 4th industrial era are required to have the four following competences. First, they should have a capability in utilizing digital tools and devices. Second, they should be able to encourage their students to master the use of technology. Third, they should be able to predict the future changes and ways to encounter them. Forth, they should be able to control themselves of the negative effect of the changes, and be able to face them by exploring new ideas, making innovations and creativity.